Unveiling Excellence: Exploring The Dynamics of Honors College Impact on Students' Personal, Professional Development, and Motivation - Absatova, Marfuga; Nurlanov, Shyngys; Bilyalov, Darkhan; Turalbayeva, Almash; Doshybekov, Aidyn; Yermakhanov, Baglan (Journal of Posthumanism, 2025)
This study aimed to investigate the influence of the Honors College at Abai Kazakh National Pedagogical University on students' personal and professional growth, motivation, and intellectual development. By employing qualitative research methods through semi-structured interviews of 14 students, the researchers assessed how the Honors College fosters holistic development, critical thinking, and cultural identity reinforcement in its students. The study also explored the challenges faced by students, such as time constraints and disinterest in the teaching profession. The findings of this research highlighted the importance of experiential learning through internships and structured programs in shaping future educational leaders. Overall, this study provides valuable insights into the effectiveness of Honors programs within the Kazakhstani educational context.